OPINI AUDIT GOING CONCERN SERTA FAKTOR-FAKTOR YANG MEMPENGARUHI - Ni Nyoman Tulia, I Ketut Sunarwijaya, I Nyoman Kusuma Adnyana Mahaputra (Accounting Profession Journal (APAJI), 2020)
Going concern audit opinion is the opinion of the auditor about whether an audited company can maintain its going concern or survival at least in the next one year. This study aims to determine whether profitability, liquidity, company size and KAP size to the possibility of receiving going concern audit opinion on the Indonesian Stock Exchange. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2015 to 2017. While the study sample used a purposive sampling method to obtain a sample of 20 companies with a total of 60 observations. The data collection method used in this study is the method of observing non participation. The type of data used in this study is secondary data. While the analysis technique used in this study is a regression analysis technique. The results of this study indicate that liquidity has a negative effect on the possibility of going concern audit opinion. Whereas profitability, company size and KAP size do not affect the possibility of going concern going audit opinion.